2023
DOI: 10.3389/fpubh.2023.1059067
|View full text |Cite
|
Sign up to set email alerts
|

Addressing COVID-19 vaccine hesitancy in rural communities: A case study in engaging trusted messengers to pivot and plan

Abstract: The pandemic declaration of COVID-19 in 2020 presented unique challenges, lessons, and opportunities for public health practice in the United States. Despite clear evidence of COVID-19 vaccine effectiveness, vaccine uptake and vaccine confidence remained low in many regions. Vaccine holdouts, or those who are vaccine hesitant, have been an increasingly difficult population to reach. Several factors influence vaccine hesitancy and behavior in rural areas, including health care access challenges, misinformation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…In our study, 11.9% of respondents had information on vaccines and vaccinations from the social media; this was very low compared to the 22.07 – 49.5% reported elsewhere in Saudi Arabia and Palestine [ 15 , 65 ]. Our finding was also different from that of a study conducted in rural communities to enhance vaccine confidence, wherein trusted messengers had lots of challenges communicating the importance of COVID-19 vaccine importance to the population [ 17 ]. In our study, there was 91.4% trust in childhood vaccination which was very high when compared with the 45.9% and 49.2% COVID-19 vaccine confidence reported amongst Filipinos and Malaysians respectively [ 66 ].…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In our study, 11.9% of respondents had information on vaccines and vaccinations from the social media; this was very low compared to the 22.07 – 49.5% reported elsewhere in Saudi Arabia and Palestine [ 15 , 65 ]. Our finding was also different from that of a study conducted in rural communities to enhance vaccine confidence, wherein trusted messengers had lots of challenges communicating the importance of COVID-19 vaccine importance to the population [ 17 ]. In our study, there was 91.4% trust in childhood vaccination which was very high when compared with the 45.9% and 49.2% COVID-19 vaccine confidence reported amongst Filipinos and Malaysians respectively [ 66 ].…”
Section: Discussioncontrasting
confidence: 98%
“…Mother’s education, has been widely reported as an important determinant of knowledge in childhood vaccination in Ethiopia, Greece, Malaysia, and Palestine [ 15 , 18 , 61 , 71 ]. On the other hand, research studies in the rural communities of the United States of America, showed that the factors affecting vaccine acceptance and knowledge were mistrust and misinformation as well as constantly changing health guidelines [ 17 ]..…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community engagement was identified as an important enabler to COVID‐19 vaccination programs which mirrored other international studies 32–36 . Tjilos et al, 34 a qualitative study of community‐engaged conversations about COVID‐19 vaccinations in New England, USA, found that community leaders suggested utilising existing social networks and trusted community leaders to disseminate credible information.…”
Section: Discussionmentioning
confidence: 60%
“…Community engagement was identified as an important enabler to COVID-19 vaccination programs which mirrored other international studies. [32][33][34][35][36] Tjilos et al, 34 a qualitative study of community-engaged conversations about COVID-19 vaccinations in New England, USA, found that community leaders suggested utilising existing social networks and trusted community leaders to disseminate credible information. This is particularly important in rural areas where such engagement plays an important role in public health responses 23 and can be utilised to ensure that programs are targeted to specific community needs rather than using a 'one size fits all' approach that often excludes marginalised groups.…”
Section: Discussionmentioning
confidence: 99%